Senam dan Penyuluhan Kesehatan: Kegiatan Pencegahan Hipertensi Pada Masyarakat Kecamatan Meranti - Arrafi Insani; Siti Fatimah; Wilda Wardani (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2022)
Hypertension was still a major health problem in Meranti Village residents. However, the high prevalence rate requires a solution for handling the hypertension promblems. In this case, gymnastics and health counseling are the most appropriate activities to overcome this problem. The purpose of this activities was to increase knowledge and awareness, as well as how to prevent hypertension among village community. The implementation method is through gymnastics and health counseling about hypertension and its risk factors, long-term impact, and how to prevent it. Gymnastic activities and hypertension counseling went well and orderly. The enthusiastic response of the community shows that the activities can be declared successful. It is hoped that the community can apply hypertension exercise and counseling materials which is obtained from this activities to achieve the higher degree of health.